Exploring the improvement of the decentralized supply chain management, its systems and processes in support of the strategic objectives of Parliament. - Okojie, Nomxolisi Nobukhosi (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.